Poorly controlled diabetes mellitus alters placental structure, efficiency, and plasticity. Issue 1 (28th June 2020) - Nteeba, Jackson; Varberg, Kaela M; Scott, Regan L; Simon, Mikaela E; Iqbal, Khursheed; Soares, Michael J
Abstract : Introduction: The hemochorial placenta provides a critical barrier at the maternal–fetal interface to modulate maternal immune tolerance and enable gas and nutrient exchange between mother and conceptus. Pregnancy outcomes are adversely affected by diabetes mellitus; however, the effects of poorly controlled diabetes on placental formation, and subsequently fetal development, are not fully understood. Research design and methods: Streptozotocin was used to induce hyperglycemia in pregnant rats for the purpose of investigating the impact of poorly controlled diabetes on placental formation and fetal development. The experimental paradigm of hypoxia exposure in the pregnant rat was also used to assess properties of placental plasticity. Euglycemic and hyperglycemic rats were exposed to ambient conditions (~21% oxygen) or hypoxia (10.5% oxygen) beginning on gestation day (gd) 6.5 and sacrificed on gd 13.5. To determine whether the interaction of hyperglycemia and hypoxia was directly altering trophoblast lineage development, rat trophoblast stem (TS) cells were cultured in high glucose (25 mM) and/or exposed to low oxygen (0.5% to 1.5%). Results: Diabetes caused placentomegaly and placental malformation, decreasing placental efficiency and fetal size. Elevated glucose disrupted rat TS cell differentiation in vitro. Evidence of altered trophoblast differentiation was also observed in vivo, as hyperglycemia affected the junctional zone transcriptome and interfered with intrauterine trophoblast invasion and uterine spiral artery remodeling. When exposed to hypoxia, hyperglycemic rats showed decreased proliferation and ectoplacental cone development on gd 9.5 and complete pregnancy loss by gd 13.5. Furthermore, elevated glucose concentrations inhibited TS cell responses to hypoxia in vitro. Conclusions: Overall, these results indicate that alterations in placental development, efficiency, and plasticity could contribute to the suboptimal fetal outcomes in offspring from pregnancies complicated by poorly controlled diabetes.